Insights into structural and proteomic alterations related to pH-induced changes and protein deamidation in hair - Adav, Sunil S. (2024)
Objectives: The hair shaft is often exposed to shampoo and haircare products that have unknown or varying pH levels. These products contain a combination of surfactants and other active ingredients to treat the hair or the scalp. As amphoteric proteins, hair keratins have limited buffering capacity, so variations in pH can have multifaceted impacts on them. However, there is limited knowledge about how pH affects keratins and keratin-associated proteins (KAPs). Therefore, this study aims to examine the effects of varying pH levels (pH 3–pH 12) on hair structure and analyse consequent alterations in the hair proteome using massspectrometry- based proteomics.